Effects of oral intoxication by lead acetate on pituitary-testicular axis in the pubertal rat (Italian Journal of Public Health, 2008)
Background: The aim of this work is to study the effects of lead on pituitary-testicular axis. It is about a direct toxicity on testicular cells or an indirect toxicity via abnormalities of the hypothalamic-pituitary axis?Methods: Forty male rats were divided equitably into four groups. One of these groups received tap water containing 0.3% lead acetate for one month. A second group was assigned to the same protocol but the intoxication was conducted for two months. The third and the fourth groups were used as reference. At the end of the experiment, the rats were anaesthetized and blood was collected for the proportioning of the FSH, the LH, testosterone and lead. The testes and epididymides were removed quickly and weighed. For the determination of testosterone in testicular fluids, a cruciate incision was made in the tunica albuginea of each right testis and centrifuged at 54xg for the extraction of interstitial fluid. Thereafter, the seminiferous tubules were extruded and centrifuged at 6000xg to collect seminiferous tubule fluid. The left testis of each animal was cut in two halves, one half was used for the histological examination and the other was suitably treated for the determination of the lead concentration. The epididymides were homogenized in solution containing Triton X-100 and spermatozoa were counted using Malessez cells. The plasma FSH and LH were determined by RIA using reagents from a commercial kit (BioInternational, France), while testosterone was determined by electrochemiluminescence (Elecsys, rochediagnostics). The lead concentration in blood and Tissues was measured by flameless atomic absorption spectrophotometry with the Zeeman effect background (Hitachi Z- 9000).Results: In the rats poisoned for one month, no notable effect was noted in spite of a blood lead concentration of 0.721 μg/ml. On the contrary, in animals exposed to lead acetate for two months, the blood level passed to 2.721 μg/ml and plasma testosterone, FSH and LH dropped by about 45%. In parallel, the secretion of testosterone by the Leydig cells fell by 35% and epididymal sperm count dropped by 14%. The histological examination showed lead deposits in the walls of the seminiferous tubules.Conclusions: Although we do not exclude a directly toxic action of lead on the interstitial cells and on the Sertoli cells, it seems that the hypothalamic-pituitary axis is the major target of lead since the decrease in the plasmatic LH and FSH was associated with a reduction in testosterone secretion and with a reduction in the number of the epididymal spermatozoa
Keywords: FSH; LH; testosterone; lead; rat; spermatozoa